FIKIH MODERATION OF RELIGION ACCORDING TO THE QUR'AN (The Role of Religious Figures in Strengthening Religious Harmony) - Zuhri, Ahmad; Yumni, Aufah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Religious moderation fiqh is an approach to the study of fiqh (Islamic jurisprudence) that emphasizes a moderate, balanced and tolerant understanding of Islamic teachings. which is indicated in the verses of the Koran. The concept of moderation in the Qur'an refers to an approach that avoids extremism, fanaticism and exaggeration (at-Tharruf ad-Dini) in dealing with religious issues. Jurisprudence of moderation promotes a complete and universal understanding that is in line with the principles of simplicity, tolerance, inclusivity and justice in understanding and practicing Islamic teachings according to the instructions and guidance of the Qur'an. In this study, the authors used library research, namely the research object, mainly commentary books and a little field approach. . Based on the objectives of this research, it includes basic research, namely research in order to broaden and sharpen theoretical knowledge and understanding. The results of the study found that religious moderation fiqh according to the Koran basically directs people to understand the deep meaning contained in the Koran regarding religious moderation as a whole and universal, not narrowly and textually. Many Muslim groups understand the text of the verses of the Koran superficially and textually, resulting in the emergence of a radical and extreme understanding that is not in accordance with the messages intended by the Koran itself. intact and universal verses of religious moderation will create harmony among religious communities, even among the religions themselves.